Pengaruh Online Customer Review dan Online Customer Rating serta Kemudahan Penggunaan terhadap Keputusan Pembelian pada Restoran yang ada di GoFood - Lavenia Christine Sulistio; Muhammad Fikry Aransyah (Universitas Batanghari, 2023)
BPS Samarinda (2022) shows that 76.55% of Samarinda residents access the internet. Digital services that have experienced increased demand, especially during the pandemic, are Online Food Delivery (OFD). GoFood leads above ShopeeFood and GrabFood as the most installed apps. The research objective was to identify the effect of online customer reviews, online customer ratings, and ease of use on purchasing decisions at GoFood restaurants in Samarinda. This research uses causal associative quantitative research. The research sample is 100 people with a purposive sampling method. Multiple linear regression models were tested with normality, multicollinearity, and heteroscedasticity tests. Furthermore, a hypothesis test was carried out, which consisted of a partial test, simultaneous test, and test of the coefficient of determination. The results of this study are that online customer reviews, online customer ratings, and ease of use significantly affect purchasing decisions both partially and simultaneously